Modern problems of computer science and IT-education - Aleksiyev, Volodymyr; Bilova, Mariia; Borysova, Natalia; Cherednichenko, Olga; Fedorchenko, Volodymyr; Goloskokov, Alexander; Goloskokova, Anna; Harasymchuk, Oleh; Havrylova, Alla; Holubnychyi, Dmytro; Ivashchenko, Oksana; Kalachova, Veronika; et al. (Premier Publishing s.r.o., Vienna, Austria, 2020)
The collective monograph highlights modern problems of development and using information technologies for resolving some issues in different domain areas. The proposed theoretical methodologies, models and practical approaches are considered and investigated in the context of IT-education, software engineering, artificial intelligence and cybersecurity. Every chapter describes methods, efficient algorithms and resolutions specific for the particular domain area and field of knowledge.
Keywords: monograph; information technology; decision-making support; transboundary emergency; mathematical models; cybersecurity; database; software; educational process; knowledge systems